Ризик та методи оцінки ризику в професії програміста - Чмутов, Ю. В. (ХНУРЕ, 2019)
The article tells about a programmer’s life safety. Here you will learn what risk is and which aspects are responsible for the treat to life in the profes-sion of a programmer. There are also describes the detailed risk assessment methodology. The article demonstrates a diagram and a table with the help of which everyone can determine the probability of a risk, its consequences and the level of danger.
Keywords: danger; risk assessment meth-odology; human health